2005
DOI: 10.1063/1.1895722
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alkyl chain length and size of the headgroups of the surfactant on solvent and rotational relaxation of Coumarin 480 in micelles and mixed micelles

Abstract: The effect of alkyl chain length and size of the headgroups of the surfactant on the solvation dynamics and rotational relaxation of Coumarin 480 (C-480) has been investigated using dynamic Stokes' shift of C-480 in different types of alkyltrimethylammonium bromide micelles and mixed micelles. The rotational relaxation time increases with increase in alkyl chain length of the surfactant. The increase in the number of alkyl chains of the surfactant leads to the more close packed micelles, hence the microviscosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
67
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(77 citation statements)
references
References 62 publications
10
67
0
Order By: Relevance
“…Despite the fact that the E T (30) values around the fluorophore in the micelles studied do not differ very much, there is a gradual decrease in the value with an increase in the hydrocarbon chain length of the cationic surfactants form DTAB to CTAB through TTAB. Chakrabarty et al, in one of their works, reported very similar micropolarities around a coumarin derivative in nTAB micelles and reverse micelles [19]. The micropolarity values in the three nTAB micellar systems estimated from the present study are close to our earlier reported values where we constructed the calibration curve from the ratio of fluorescence intensities of the two prototropic forms of the proton transfer probe norharmane (NHM) [7].…”
Section: Steady-state Absorption and Fluorescencesupporting
confidence: 85%
See 4 more Smart Citations
“…Despite the fact that the E T (30) values around the fluorophore in the micelles studied do not differ very much, there is a gradual decrease in the value with an increase in the hydrocarbon chain length of the cationic surfactants form DTAB to CTAB through TTAB. Chakrabarty et al, in one of their works, reported very similar micropolarities around a coumarin derivative in nTAB micelles and reverse micelles [19]. The micropolarity values in the three nTAB micellar systems estimated from the present study are close to our earlier reported values where we constructed the calibration curve from the ratio of fluorescence intensities of the two prototropic forms of the proton transfer probe norharmane (NHM) [7].…”
Section: Steady-state Absorption and Fluorescencesupporting
confidence: 85%
“…Rotational diffusion of two ionic lipophilic fluorophores in alcohol and in SDS, CTAB, and TX-100 micellar environments was reported by Quitevis et al and the study has presented a detailed picture of the structural and dynamical aspects of the probes in micelle-water interfaces [22]. Study of the effect of hydrophobic chain length of surfactants on the dynamical behavior of a fluorophore was started rather recently [19][20][21]. Chakrabarty et al have reported the effect of varying chain length as well as head group of cationic surfactants on the rotational relaxation of coumarin 480 in micellar and mixed micellar environments [19].…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations